Kualitas Website atau Promosi yang Mempengaruhi Minat Beli Konsumen di Onlineshop? - Ratih Hadiantini; Samino Samino (Economics Professional in Action (E-Profit), 2020)
Indonesia as a country with the fastest development in e-commerce in the world has encouraged very tight competition between entrepreneurs. So demanding online business managers to be more observant in attracting Buy Interest on e-commerce websites. Buying interest can be influenced by Website Quality and Promotion. Trubus shop which is a modern agricultural shop that has a chain of offline stores in several cities in Indonesia, to expand its market Trubus stores take the initiative to develop their market in online business through websites. This study aims to determine the Effect of Website Quality, Promotion and Purchase Interest in Trubus Online Shop. The research method used is descriptive method with a quantitative approach. The collected data is then managed and analyzed using statistical tests. Based on the results of data processing, partially the quality of the website has no effect on buying interest, whereas promotion has a positive effect on buying interest